Pengaruh Profesionalisme, Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai PDAM Kabupaten Muna - Hasrina Hasrina; Alida Palilati; Laode Asfahyadin Aliddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study was to determine the effect of: 1) The influence of Professionalism, Organizational Commitment and Job Satisfaction have an effect on employee performance. 2) The influence of professionalism on employee performance. 3) The effect of organizational commitment on employee performance. 4) The effect of job satisfaction on employee performance. The research method is using quantitative research. The data used are secondary and primary data. Data analysis used SPSS version 20 software. The sampling technique used a census sample of 42 employees of PDAM Muna Regency. The results showed that; 1) professionalism, organizational commitment and job satisfaction simultaneously have a positive and significant effect on employee performance. 2) professionalism has a positive and significant effect on employee performance. 3) organizational commitment has a positive and significant effect on employee performance. 4) job satisfaction has a positive and significant effect on employee performance.